Bio-vaterite formation by glycoproteins from freshwater pearls - Natoli, Antonino (2010)
A 48 kDa acidic and putative calcium-binding glycoprotein was isolated from pearls of the freshwater mussel Hyriopsis cumingii. This protein was compared with a related 46 kDa polypeptide, obtained from the nacreous shell of the same species. Separation by two-dimensional gel electrophoresis revealed that the difference in molecular weight is due to the higher extent of glycosylation of the 48 kDa protein existing in pearls. Evidence is presented that the sugar moieties of the protein contribute to crystal growth, starting with the nucleation step. In in vitro precipitation experiments, the 48 kDa glycoprotein of pearls directed the formation of round-shaped vaterite crystals while the 46 kDa glycoprotein of shells promoted formation of small irregular calcite particles. Furthermore, both proteins, 48 kDa/46 kDa, comprised carbonic anhydrase activity that has been implicated in CaCO3 formation. Thus, a function of the isolated glycoproteins in biomineralization is proposed together with the mechanism by which they can stabilize different calcium carbonate polymorphs.